Pengaruh Pengungkapan Tata Kelola Perusahaan terhadap Akurasi Harga Saham pada Perusahaan yang Terdaftar di Bursa Efek Indonesia Tahun 2013-2017 - Harsono, Budi; Saputra, Edwin (Global Financial Accounting Journal, 2019)
This study was conducted to analyze the effect of corporate governance disclosure to Share Price Accuracy. The variables of corporate governance disclosure in this study are divided into two namely Mandatory Corporate Governance Disclosure and Voluntary Corporate Governance Disclosure. The data obtained in this research is secondary data. The Secondary data used are financial statement data and company annual report data. Secondary data can be downloaded from Indonesian stock exchanges official website via www.idx.co.id. The number of companies used as research samples are 393 companies. The study period began from 2013 to 2017. The data obtained were as many as 1965 data. The conclusion of this study prove that both of the independent variables have a significant effect to Share Price Accuracy.Mandatory Corporate Governance Disclosure has a significant positive effect to the Share Price Accuracy partially.Voluntary Corporate Governance disclosure also has significant effect to the Share Price Accuracy partially.